Penerapan CSR (Corporate Social Responsibility) Perbankan Syari’ah Umum di Indonesia Perspektif Maqasid Asy Syari’ah - Muhammad Iqbal (University of Darussalam Gontor, 2017)
The practice of CSR has been a trend among corporation for the last few years. The implementation of CSR in a financial institution, however, still adopts the western concept. Previous studies have also found that the practice of CSR in today’s corporations in not in with Islamic sharia. This is closely related to the concept of CSR in which the practice follows the original concept. The researcher planned to observe general sharia banks in Indonesia, particularly their CSR practice. This study used the perspective of maqāsid asy syari’ah in order that the legitimacy of CSR practice could be undeniable, the quality would approve, and the implementation could be more serious more than the previous-years’ ones. The observation on the practice of CSR in sharia commercial banks would be focused on two sharia commercial banks as the representing samples of 12 sharia commercial banks in Indonesia. Thin was deemed necessary because in reality not all sharia commercial banks have been able to implement and report good practice of CSR. The reality and result in the field showed that from the persective of maqāsid asy syari’ah focusing on the kulliyatul khams standar. Bank Muamalat Indonesia and Bank Syariah Mandiri have included most of the standard. In other words, the justification of maqāşid asy syari’ah in the oractice of CSR for the benefit of the people. The generalization of population result represented by the two sharia commercial banks could be formed if the practice in the other banks was a similar or even more than that in these sample banks.